Adaptive Management and Social Capital in Rural Islamic Boarding School Enrollment Growth: A Qualitative Case Study from Tebo Regency, Indonesia - Sri Wahyuni; Andryadi; Wiwin Narti (At Turots: Jurnal Pendidikan Islam, 2021)
Rural Islamic boarding schools (pesantren) in Indonesia face persistent enrollment volatility amid accelerating modernization, digital transformation of educational information-seeking, and intensified competition with credentialed formal schools. Existing scholarship has examined either conventional promotion or digital marketing in pesantren contexts, yet integrative analyses linking sociocultural ties, managerial decisions, and geographic-economic conditions remain limited. This study examines how Pondok Pesantren Darussalamah, located in a remote sub-district of Tebo Regency, Jambi Province, sustained enrollment growth from six students at its founding in 2011 to approximately 120 students by 2025. A descriptive qualitative case-study design was adopted. Data were collected between May and August 2025 through participant observation of daily and recruitment activities, semi-structured in-depth interviews with eight informants selected by purposive sampling (the head of the pesantren, three teachers, two active students, one alumnus, and one parent representative), and documentary review of brochures, social-media archives, and enrollment records spanning 2011–2025. Analysis followed the Miles and Huberman interactive model; credibility was secured through source and method triangulation, member checking, and prolonged engagement. Enrollment growth was sustained by five interlocking practices: relational engagement with the surrounding community, affordable-tuition and scholarship policies, integrated formal-religious curriculum with disciplinary structure, character-oriented extracurricular programs, and hybrid socio-religious–digital promotion. Persistent constraints included inadequate facilities, weak data-driven planning, geographic remoteness, and heterogeneous community religious perceptions. Mitigation depended on alumni-mediated social capital, hybrid promotion, economic affirmation, and incremental managerial professionalization. The findings suggest that recruitment success in rural pesantren depends less on formal marketing intensity than on relational legitimacy, managerial adaptability, and inclusive access policies.